The Use of Jigsaw Strategy on Students’ Speaking Ability in Expressing Gratitude and Appreciation - Herawati Bukit; Sarma Dewi Kemala. S; Sabar Manik; Himpun Panggabean (English Lecturers and Teachers Association (ELTA), 2023)
The purpose of this research was to identify the effectiveness of jigsaw strategy on students' speaking ability in expressing gratitude and appreciation. This study employed a quantitative research design and involved two groups of students: the experimental group and the control group. The experimental group was taught using the Jigsaw Strategy, while the control group received instruction without jigsaw strategy. The population of the research consisted of 60 students from the second grade of SMP Singosari Delitua, and a purposive sample technique was applied where 30 students was selected as control group and another 30 students were selected as experimental group. Speaking tests, including pre-tests and post-tests, were used to collect the data for both groups. In the control group, the mean deviation was 8.87, indicating a low level of improvement. This group was taught without the Jigsaw Strategy. On the other hand, the experimental group taught using the Jigsaw Strategy, had a mean deviation of 23.03, showing a higher level of improvement. As a result, it was concluded that the Jigsaw Strategy had a significant impact on students' speaking achievement in expressing gratitude and appreciation. Based on the information provided, this research can be considered an effective approach to the teaching and learning process. Keywords: Speaking, Appreciation, Gratitude, Jigsaw Strategy